(untitled) (Research, Society and Development, 2022)
Objective: To analyze the cause of premature aging in rural workers. Methodology: This is a literature review whose theoretical basis was structured through research and analysis of books, journals and articles published in scientific journals in the database Periódicos Capes, Scielo, Pubmed and Google Scholar. Results: Residents of rural areas are more likely to develop premature aging, as they perform most of their work activity outdoors, are exposed to the sun for long hours without any protection against ultraviolet radiation, solar radiation, the biggest cause of cancer. Conclusion: The results of this study showed that it is necessary to develop actions such as educational programs and thus alert rural workers to the risks of exposure to UVR, specifically photo-aging.